PERANAN TIM EVALUASI PENGAWASAN PENYERAPAN ANGGARAN DALAM PERCEPATAN PENYERAPAN ANGGARAN PENDAPATAN BELANJA DAERAH PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI KALIMANTAN TIMUR - Median Canserio (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research examines the role of the team evaluation absorption budgeting control in acceleration local government budget on Regional Development Agency of East Kalimantan Province. Based on the research we concluded that the role of the evaluation team monitoring budget spending has not fully in place to improve targer realization of budget absorption, as influenced by three factors namely: First, reporting implementation budget spending to policy holders in adsministrasi, Second, commitment on each SKPD leadership in carrying out the process of accelerating absorption in the scope of Bappeda of East Kalimantan Province, Third, reward and punishment for each apparatus and leadership in every SKPD in the scope of the Provincial Government of East Kalimantan, particularly in East Kalimantan Provincial Bappeda.